CRIMINAL LAW POLICY IN HEALTH CARE - Agustina, Enny (Faculty of Law Universitas Panca Bhakti, 2019)
Legislation in the health sector must always follow and fulfill the community needs. After that, it must be able to answer the problems of the community in the health sector, so that people feel at ease as citizens. It is the duty of the government so that people can enjoy health care at affordable costs. In addition, hospitals must always maintain their professionals. The problem this paper about how is criminal law policy in health care and the methods is Normative legal research is research conducted by examining library materials. This research on normative literature includes research on legal principles, research on legal systematic, research on the levels of vertical and horizontal synchronization, comparison of law and legal history. The result is obtained are in addition to criminal law, namely Law Number 1 Year 1946 on the Criminal Code, there are also several criminal policy that regulate criminal law protection in health care or medical. The laws and regulations are Law Number 36 Year 2009 on Health, Law Number 44 Year 2009 on Hospitals, Law Number 29 Year 2004 on Medical Practice and many other laws and regulations related to criminal policy in the health sector. Since ancient Greece, legal science has touched almost all aspects of human life, except the medical field. Health workers who existed at that time regulated their own work methods with professional codes of ethics and oaths that were deeply rooted in tradition and had a strong influence on society.